Achieving high-performance p-type SmMg2Bi2 thermoelectric materials through band engineering and alloying effects. Issue 31 (28th January 2020) - Saparamadu, Udara; Tan, Xiaojian; Sun, Jifeng; Ren, Zhensong; Song, Shaowei; Singh, David J.; Shuai, Jing; Jiang, Jun; Ren, Zhifeng
Abstract : P-type SmMg2 Bi2, a new member of Bi-based 1-2-2 Zintl family, has been investigated and demonstrated to be a promising material for application in TE power generation. Abstract : Thermoelectric Zintl phases have attracted increasing attention in the past few decades, with good thermoelectric performance observed in many different families. Due to their intrinsic low lattice thermal conductivity, p-type CaAl2 Si2 (1-2-2)-type Zintl phases, which also exhibit relatively higher electrical transport performance, have been demonstrated to be promising thermoelectric materials for mid- to high-temperature applications. Here we investigate the thermoelectric performance of p-type SmMg2 Bi2, a new member of this 1-2-2 Zintl family. Band structure calculations reveal that the calculated band gap of SmMg2 Bi2 is smaller in comparison to that of other Bi-based Zintl phases, which inevitably contributes to the bipolar effect clearly observed at higher temperature. Further successful substitution of Eu and Yb is effective in suppressing the bipolar effect and ensures achievement of superior electronic performance, resulting in a peak figure of merit ( ZT ) of ∼0.9 at 773 K. The current work has successfully expanded the family of Bi-based p-type 1-2-2 Zintls, and could play an essential role in stimulating further investigation of other Zintl compounds.